Assistance in Cost Classification and Cost Production of Street Food Microenterprises in Bekasi District - Neng Asiah; Hendri Kartika Andri; Sabaruddinsah; Amara Pristania Nandita; Aisah Indah Safitri (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
MSMEs are considered the main pillar of the economy, especially when large companies experience difficulties or bankruptcy. This is considered positive because MSMEs can be the main indicator of regional economic progress. However, some MSME players may not understand how to develop their products, especially in classifying and calculating costs. One strategy in business development is to make a detailed cost classification or calculation of production costs in an activity report. This activity aims to provide practical guidance, training and mentoring in classifying costs and calculating production costs for MSMEs in the Mustika Jaya forum, especially